Autocuidado na percepção de pessoas com hanseníase sob a ótica da complexidade - Souza, Ioná Araújo de [UNESP]; Ayres, Jairo Aparecido [UNESP]; Meneguin, Silmara [UNESP]; Spagnolo, Regina Stella [UNESP] (My University, 2014)
Objective: This study aimed to understand how patients with Hansen's Disease perceive self-care from the complexity perspective. Methods: Qualitative, descriptive and exploratory study based on the Collective Subject Discourse. Results: Sample composed of 15 subjects, most of whom were married males (66.6%) with a mean age of 52.3 years and were classified in the polarized forms of the disease. The following themes emerged from the DCS synthesis: having Hansen's Disease, drug therapy, self-care and lifestyle. The study provided visibility to the vertical model, which is largely hegemonic in the tradition of public health care policies, showing concern about only treating the disease, disregarding the complex relationships involved. Conclusion: Acknowledging these limitations and setting strategies to change them in favor of the dialogue among interprofessional team members are challenges to further develop self-care practices and to empower patients in relation to treatment and disease.

Objetivo: Comprender la percepción de las personas con lepra en relación con el autocuidado bajo la óptica de la complejidad. Métodos: Investigación cualitativa, descriptiva y exploratoria, con base en el Discurso del Sujeto Colectivo. Resultados: Muestra constituida por 15 sujetos, mayoría masculina (66,6%), edad media 52,3 años, casados (66,6%) y clasificados en las formas polarizadas de la enfermedad. Por la síntesis del DSC, emergieron los temas: ser portador de lepra; terapéutica medicamentosa; autocuidado; estilo de vida. El estudio le dio visibilidad al modelo verticalizado, largamente hegemónico en la tradición de las políticas públicas de salud, mostrando preocupación en tratar solamente la enfermedad y desconsiderando las relaciones complejas que la involucran. Conclusión: Reconocer estas limitaciones y tener estrategias para transformarlas en favor del diálogo entre los miembros del equipo interprofesional son retos para hacer avanzar las prácticas del autocuidado y del empoderamiento del portador en relación con el tratamiento y la enfermedad.

Objetivo: Compreender a percepção das pessoas com hanseníase em relação ao autocuidado, sob a ótica da complexidade. Métodos: Pesquisa qualitativa, descritiva e exploratória alicerçada no Discurso do Sujeito Coletivo (DSC). Resultados: Amostra constituída de 15 sujeitos, idade média de 52,3 anos, maioria masculina (66,6%), casados (66,6%) e classificados nas formas polarizadas da doença. Pela síntese do DSC emergiram os temas: ser portador de hanseníase, terapêutica medicamentosa, autocuidado e estilo de vida. O estudo deu visibilidade ao modelo verticalizado, largamente hegemônico na tradição das políticas públicas de saúde, mostrando preocupação em tratar apenas a doença, desconsiderando as relações complexas que a envolve. Conclusão: Reconhecer estas limitações e ter estratégias para transformá-las em favor do diálogo entre os membros da equipe interprofissional são desafios para fazer avançar as práticas do autocuidado e do empoderamento do portador em relação ao tratamento e à doença.
Hansen's disease patients' perception of self-care from the complexity perspective
Autocuidado en la percepción de las personas con enfermedad de hansen en la óptica de la complejidad
Keywords: Hansen's disease; Leprosy; Self care; Philosophy in nursing; Enfermedad de Hansen; Lepra; Autocuidado; Filosofía en enfermería.; Hanseníase; Lepra; Autocuidado; Filosofia em enfermagem